The ethnic food system of Jaad Bhotiya tribal community in the Gangotri landscape of western Himalaya: a transition in traditional practices. (June 2023) - Bhatt, Shobha; Purohit, Monika Vats; Balodi, Khima Nand; Kumar, Ujjwal; Sharma, Archana; Shridhar, Vijay; Arunachalam, Ayyanadar; Arunachalam, Kusum
Traditional foods of Indigenous peoples are composed of ingredients from the local environment that are culturally acceptable. The Indian Himalayan region is known for its diverse tribal population, and each of them exhibits a distinct food culture. The present study has been conducted first time to document the diverse traditional food practices of Jaad Bhotiya, a lesser-known tribe of the Gangotri landscape, Uttarakhand, India. The community holds a varied range of ethnic foods; however, 13 traditional dishes are described in the present article. This study reflects a clear understanding of their preference, importance, and causes of transitions. It is noteworthy that the elders were highly attached to ethnic foods while the younger generation has limited fondness for it. The current transitional pattern is an issue of concern for policymakers, anthropologists, and the community itself. Nonetheless, a holistic policy approach to conserve traditional foods may provide an opportunity to sustain these unique practices.